Optimalisasi Partisipasi Masyarakat Dalam Pembangunan di Desa Bangkit Baru Kabupaten Barito Kuala - Ismawati; Sri Hidayah; Fachreza Aditya Ramadhanie; Alkhairul Huda; Rezky Amalia; Taufin Rahmawan; Kartika Sindi Mahdalena; Lolla Apriliana Offianita (Prodi Sosiologi FISIP ULM, 2023)
Village development is an inseparable part and plays a very important role in realizing the achievement of regional and national development. The lack of awareness and understanding of the Bangkit Baru Village community to be involved in development is the main obstacle to community-based village development in this village. The Covid-19 pandemic is the main factor that has driven community participation to decline. This is the background for the volunteer team to optimize community participation in village development in the era of the Covid-19 pandemic in Bangkit Baru Village. The purpose of this service is to increase community awareness and understanding of the importance of their participation in village development. In addition, this program also focuses on making the people of Bangkit Baru Village able to participate directly in every activity carried out with the volunteer team. The implementation method used is a participatory approach and community development. The work programs implemented include: mutual cooperation, entrepreneurship, planting family medicinal plants by utilizing yard land, activating religious activities, activating security activities, and counseling conducted to schools in Bangkit Baru Village. Based on the results obtained during the service period, it shows that the awareness and understanding of the Bangkit Baru Village community towards participation in developing the village is increasing. The community realizes and understands the importance of their role in village development. This can be seen from the enthusiasm and activeness of the community in participating and contributing to the program run by the volunteer team. The increased awareness and understanding gained in this service program can make the community in the future more actively participate and contribute to jointly build the village with social solidarity between communities.